THEORETICAL FUNDAMENTALS OF SPIRITUALITY FORMATION JUNIOR SCHOOL STUDENT IN THE EDUCATIONAL PROCESS (Pedagogy of Higher and Secondary Education, 2007)
Nowadays, it's impossible to adequately bring up. The generation able to build a humanistic society without children beaming of the norms of moral culture. Teaching be based on Ukrainian national traditions of respect of old people. There traditions bring up the sense of national dignity tolerance.